2011
DOI: 10.1175/2011jas3617.1
|View full text |Cite
|
Sign up to set email alerts
|

Do We Observe Aerosol Impacts on DSDs in Strongly Forced Tropical Thunderstorms?

Abstract: Rain drop size distributions retrieved from polarimetric radar measurements over regularly occurring thunderstorms over the islands north of Darwin, Australia, are used to test if aerosol contributions to the probability distributions of the drop size distribution parameters (median volume diameter and normalized intercept parameter) are detectable. The observations reported herein are such that differences in cloud properties arising from thermodynamic differences are minimized but even so may be a factor. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 34 publications
11
32
0
Order By: Relevance
“…This is likely associated with local atmospheric aerosols and/or moisture. Recently, May et al (2011) used polarimetric radar measurements to examine the effects of aerosols on DSDs of thunderstorms in Darwin. Their results showed that high aerosol concentrations could lead to a lower NW and higher Dm compared with low aerosol concentration conditions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This is likely associated with local atmospheric aerosols and/or moisture. Recently, May et al (2011) used polarimetric radar measurements to examine the effects of aerosols on DSDs of thunderstorms in Darwin. Their results showed that high aerosol concentrations could lead to a lower NW and higher Dm compared with low aerosol concentration conditions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Other more recent modeling and observational studies have shown that enhanced aerosol concentrations lead to fewer, larger raindrops in warm-phase (Altaratz et al 2008;Berg et al 2008;Saleeby et al 2010) and convective clouds (Storer et al 2010;May et al 2011;Lim et al 2011;Khain et al 2011;Storer and van den Heever 2013;Loftus and Cotton 2014). These studies attribute the larger raindrops to greater rain accretion rates due to higher cloud water contents in polluted clouds compared with clean clouds, as well as to the shedding and melting of larger hailstones.…”
Section: Introductionmentioning
confidence: 90%
“…Only in the case of CE, where no flow direction is dominant, did R, D m , and N exhibit high values, which might indicate a high availability of both CCN and water content. May et al [89] reported a large number of small drops for high aerosol regimes, but an inverse relation between rain concentration and aerosol concentration in convective clouds. According to Cecchini et al [90], an increase in CCN leads to higher rain drop concentrations in stratiform rain, and larger rain droplets in convective rain.…”
Section: Rain Microstructurementioning
confidence: 99%